Border Crossing and the Logics of Space: A Case Study in Pro-Environmental Practices - Uzzell, David; Räthzel, Nora (Frontiers in Psychology, 2018)
We investigate whether and how workers in a transnational oil corporation carry practices, meanings, and identities between the places of work and home, focusing on environmental and health and safety practices, in order to understand the larger question, how can environmentally relevant practices be generalized in society at large? Our theoretical starting point is that societal institutions function according to different logics (Thornton et al., 2012) and the borders (Clark, 2000) between these institutions create affordances and constraints on the transfer of practices between these places. By connecting their theoretical ideas, we suggest that these provide an alternative critique and explanatory account of the transfer of environmental practices between home and work than a “spillover” approach. We employ life history interviews to explore the development and complexity of the causes, justifications, and legitimations of people’s actions, social relationships, and the structural constraints which govern relationships between these spaces. While Clark’s concepts of permeable, strong, or blended borders are useful heuristic tools, people may simultaneously strengthen, transgress, or blend the borders between work and home in terms of practices, meanings, identities, or institutional logics. Individuals have to be understood as creators of the border crossing process, which is why their life histories and the ways in which their identities and their attachments to places (i.e., institutions) are shaped by the logics of these places are important. For environmental practices to travel from work to home, they need to become embedded in a company culture that allows their integration into workers’ identities.